2011
DOI: 10.4028/www.scientific.net/amr.275.73
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Strengths of Mg Alloy AZ31B-H24 Friction Stir Lap Welds

Abstract: The effects of selected friction stir lap welding parameters on fracture strength of Mg alloy AZ31B-H24 welds have been studied. Rotation speed has been found to affect significantly the flow related hook size formation. Furthermore, fracture strength decreased almost linearly with hook size. A small amount of softening was detected in fracture location that was outside the nugget zone and thus this softening may only adversely affect the fracture strength slightly. Finally, simulation results are presented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…26 With the current welded material having an average grain size of ,8?6 mm, the fracture strength of the current welds is expected to be in the range of 200-275 MPa, since these are the lower and upper bounds of tensile strength corresponding to the easy activation or full suppression of the basal slip. Specimens tested under AS loading also exhibit a linear relationship with the EST by comparing current data with those (similar hooking geometry) of Chen et al 27 However, the fracture strength based on the best linear fit is significantly smaller than what can be inferred from previous defect free specimen tensile testing. 26 The stress concentration at the tip of the hooking feature is likely the reason for the lower computed fracture strength for AS loading.…”
Section: Lap Shear Fracture Load Of Friction Stir Lap Jointsmentioning
confidence: 51%
See 2 more Smart Citations
“…26 With the current welded material having an average grain size of ,8?6 mm, the fracture strength of the current welds is expected to be in the range of 200-275 MPa, since these are the lower and upper bounds of tensile strength corresponding to the easy activation or full suppression of the basal slip. Specimens tested under AS loading also exhibit a linear relationship with the EST by comparing current data with those (similar hooking geometry) of Chen et al 27 However, the fracture strength based on the best linear fit is significantly smaller than what can be inferred from previous defect free specimen tensile testing. 26 The stress concentration at the tip of the hooking feature is likely the reason for the lower computed fracture strength for AS loading.…”
Section: Lap Shear Fracture Load Of Friction Stir Lap Jointsmentioning
confidence: 51%
“…Given that the loading condition is complex during lap shear testing as a result of specimen reorientation, which generally introduces bending to the shear test, a tensile dominated fracture mode is necessary for high fracture loads. Figure 10 is a plot of fracture load per unit width as a function of EST for tool B in both RS and AS loading 27 However, the fracture strength based on the best linear fit is significantly smaller than what can be inferred from previous defect free specimen tensile testing. 26 The stress concentration at the tip of the hooking feature is likely the reason for the lower computed fracture strength for AS loading.…”
Section: Lap Shear Fracture Load Of Friction Stir Lap Jointsmentioning
confidence: 78%
See 1 more Smart Citation
“…Our study on FSLW had earlier also extended to magnesium to magnesium alloy (Mg-to-Mg) [9]. The study has suggested that although these is a similarity in the general trend of rotation speed (ω) and forward speed (v) affecting h for both Al-to-Al and Mgto-Mg FSLW the effects of hooking on fracture strengths of the welds are significantly different.…”
Section: Introductionmentioning
confidence: 84%
“…Values of F m /w s for Al-to-Al and Mg-to-Mg FSL welds [8,9] are replotted as a function of h in Figure 7. For Al-to-Al welds, as a comparison, the range of F m /w s values of FS bead-on-plate samples, which should represent defect-free butt welds, is provided.…”
Section: Al-to-al and Mg-to-mg Weldsmentioning
confidence: 99%